Indigenous Cellulosic Raw-materials for the Production of Pulp, Paper and Board - Part II.-pulps for Writing and Printing Papers from the Castor Oil Plant (Rioinus oommunis) - Bhat, R. V. (Indian Forester, 1951)
No abstract